ACUPRESSURE AND DYSMENORHORE EXERCISES IN ADOLESCENT WOMEN THOSE EXPERIENCED BY DYSMENORHORE: ACUPRESSURE AND DYSMENORHORE EXERCISES IN ADOLESCENT WOMEN THOSE EXPERIENCED BY DYSMENORHORE - Hikmanti, Arlyana; Linda Yanti; Susilo Rini (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Dysmenorrhea during menstruation which is accompanied by nausea and vomiting, low back pain, fatigue, headaches and pain that radiates to the waist can interfere with daily activities. Acupressure and dysmenorrhoea exercises are non-pharmacological therapies to reduce pain and have the effect of reducing pain. The aim of this case study is to determine the reduction in dysmenorrhea pain scale using acupressure and dysmenorrhea exercises. This research method is descriptive with a pre-post test design approach. The sample in this study was 10 young women who experienced dysmenorrhea, taken based on inclusion and exclusion criteria. The data collection technique in this study was that the researcher carried out anamesis, physical examination, and assessment of the dysmenorrhea pain scale. Acupressure and dysmenorrhea exercises were carried out and evaluated for 3 days in 3 meetings using NRS. The results of the study showed that all respondents experienced a decrease in the moderate dysmenorrhea myeri scale to mild after doing acupressure or dysmenorrhea exercises. In conclusion, acupressure or pregnancy exercise can reduce the pain scale in adolescents with dysmenorrhea. Keywords: dysmenorrhea, acupressure, exercise